Proof that for Poisson independent processes with $0<s<t$,

$$P[x(s)=k | x(t)+y(t)=n]$$

has binomial distribution


With $p=\frac{\lambda_x}{\lambda_x+\lambda_y}\frac{s}{t}$


It is proved by Bayes and Total Probability Theorems that for $x$ and $y$ Poisson independent processes and $0<s<t$:

$$P[x(t)=k | x(t)+y(t)=n]$$


$$P[x(s)=k | x(t)=n]$$

have binomial distribution as having $k$ successes in $n$ tries with success provabilities respectively $p=\frac{\lambda_x}{\lambda_x+\lambda_y}$ and $\frac{s}{t}$.


Both results you specified in "TIPS" follow from the observation that if $A$ and $B$ are independent Poisson r.v.s with parameters $a$ and $b$, respectively, the conditional distribution of $A$ given $A+B=n$ is binomial, with parameters $a/(a+b)$ and $n$. To see this, use the fact that $A+B$ is Poisson with parameter $a+b.$ Then the expression $$P(A=k|A+B=n)=\frac{P(A=k, A+B=n)}{P(A+B=n)} = \frac{P(A=k, B=n-k)}{P(A+B=n)}$$ evaluates to $$P(A=k|A+B=n)=\frac{P(A=a)P(B=n-k)}{P(A+B=n)}=\frac{e^{-a}a^k}{k!}\frac{e^{-b}b^{n-k}}{(n-k)!}\big/\frac{e^{a+b}(a+b)^n}{n!}$$ which simplifies to the stated binomial probability.

To apply this to the observations at hand, take $A=x(t)$ and $B=y(t)$ in the first instance, and $A=x(s)$ and $B=x(t)-x(s)$ in the second. Note that $x(t)-x(s)$ is independent from $x(s)$ because of the Poisson memoryless property and their parameters are $\lambda_xs$ and $\lambda_x(t-s)$.

Similarly you can prove your question by taking $A=x(s)$ and $B=x(t)+y(t)-x(s)$, so that the binomial probability success becomes:


| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.